3D Ultrastructural Study of Synapses in the Human Entorhinal Cortex. (4th September 2020) - Domínguez-Álvaro, M; Montero-Crespo, M; Blazquez-Llorca, L; DeFelipe, J; Alonso-Nanclares, L
Abstract: The entorhinal cortex (EC) is a brain region that has been shown to be essential for memory functions and spatial navigation. However, detailed three-dimensional (3D) synaptic morphology analysis and identification of postsynaptic targets at the ultrastructural level have not been performed before in the human EC. In the present study, we used Focused Ion Beam/Scanning Electron Microscopy to perform a 3D analysis of the synapses in the neuropil of medial EC in layers II and III from human brain autopsies. Specifically, we studied synaptic structural parameters of 3561 synapses, which were fully reconstructed in 3D. We analyzed the synaptic density, 3D spatial distribution, and type (excitatory and inhibitory), as well as the shape and size of each synaptic junction. Moreover, the postsynaptic targets of synapses could be clearly determined. The present work constitutes a detailed description of the synaptic organization of the human EC, which is a necessary step to better understand the functional organization of this region in both health and disease.